Tracing the evolutionary history of hepatitis B virus genotype H endemic to Mexico - Jose-Abrego, Alexis; Roman, Sonia; Laguna-Meraz, Saul; Rebello-Pinho, João Renato; Justo Arevalo, Santiago; Panduro, Arturo (Frontiers in Microbiology, 2023)
Hepatitis B virus (HBV) spreads efficiently among all human populations worldwide. HBV is classified into ten genotypes (A to J) with their geographic distribution and clinical features. In Mexico, HBV genotype H is the leading cause of hepatitis B and has been detected in indigenous populations, suggesting that HBV genotype H may be native to Mexico. However, little is known about the evolutionary history of HBV genotype H. Thus, we aimed to determine the age of HBV genotype H in Mexico using molecular dating techniques. Ninety-two HBV sequences of the reverse transcriptase (RT) domain of the polymerase gene (~1251 bp) were analyzed; 48 were genotype H, 43 were genotype F, and the oldest HBV sequence from America was included as the root. All sequences were aligned, and the most recent common ancestor (TMRCA) time was calculated using the Bayesian Skyline Evolutionary Analysis. Our results estimate a TMRCA for the genotype H in Mexico of 2070.9 (667.5-4489.2) years before the present (YBP). We identified four major diversification events in genotype H, named H1, H2, H3, and H4. The TMRCA of H1 was 1213.0 (253.3-2638.3) YBP, followed by H2 1175.5 (557.5-2424.2) YBP, H3 949.6 (279.3-2105.0) YBP, and H4 1230.5 (336.3, 2756.7) YBP. We estimated that genotype H diverged from its sister genotype F around 8140.8 (1 867.5-18 012.8) YBP. In conclusion, this study found that genotype H in Mexico has an estimated age of 2070.9 (667.5-4489.2) YBP and has experienced at least four major diversification events since then.